VD_FINDINFO HC / 2013 / 52 vom 21. Januar 2013 - VD Tribunal cantonal (2013)
EXPULSION DE LOCATAIRE, BAIL À LOYER, PROCÉDURE SOMMAIRE, DEMEURE DU DÉBITEUR, REPRÉSENTATION, UNION CONJUGALE, CONSORITÉ | 166 CC, 257d CO, 257 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 70 al. 2 CPC (CH)